Novel dual-phase Ce0.8Gd0.2O2−δ – Gd1-xCexFe1-yCoyO3 composite oxygen transport membrane - Liudmila Fischer; Nawar Haddad; Ke Ran; Stefan Baumann; Doris Sebold; Joachim Mayer; Jürgen Dornseiffer; Arian Nijmeijer; Olivier Guillon; Wilhelm A. Meulenberg (Open Ceramics)
Oxygen Transport Membranes with mixed oxygen ionic-electronic conductivity are investigated for in-situ oxygen separation in various processes such as oxy-combustion or catalytic membrane reactors enabling process intensification. Dual-phase composite membranes are of high interest due to the opportunity selecting thermo-chemical stable phases conducting oxygen ions and electrons separately. Recently, we reported a novel composite utilizing a donor doped gadolinium ferrite Gd0.85Ce0.15Fe0.75Co0.25O3 as electronic conductor. Here, the composition of this perovskite system is systematically varied and its structural as well as functional properties are investigated. Moreover, the option of a cobalt-free composition is investigated.